Effects of utilizing self-regulated learning-based instruction on EFL students’ academic writing skills: a mixed-method investigation - Anggraeni, Candradewi Wahyu; Mujiyanto, Januarius; Rustipa, Katharina; Widhiyanto (Asian-Pacific journal of second and foreign language education, 2025)
Despite the growing prevalence of Self-Regulated Learning in education, its application in writing contexts to enhance students’ academic writing skills still needs to be explored and warrants urgent attention. Owing to this, the current study scrutinized the effectiveness of self-regulated learning-based instruction and regular writing instruction on academic writing skills among university EFL students with varying self-efficacy levels and explored the students’ voices regarding the effectiveness of these two instructional models. This study applied experimental research and a case study in the explanatory sequential mixed-methods framework. Descriptive statistics and paired sample t-tests were utilized to examine the quantitative data of tests and questionnaires. At the same time, a thematic analysis was conducted to explore the qualitative data of observations, writing diaries, and semi-structured interviews. The results revealed that self-regulated learning-based instruction effectively enhanced academic writing skills across different self-efficacy levels while uncovering its benefits and challenges. This study has notable practical implications, providing valuable insights to educators, researchers, and practitioners in education, language learning, and writing instruction.